Analysis of scores and arrow grouping at major international archery competitions - Park, J. L.; Larven, J. E. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
Archers lose score for a variety of reasons. While some of those have been studied, there appears to have been little consideration of their relative importance. Archers` scores and arrow groups on the target were analysed at two of the major international tournaments held during 2013. It was found that many archers lose score through incorrectly adjusting their sights, which can have a major impact on their final placing in the event. It was also found that as the archer`s ability improves, so does the relative importance of factors with regard to their equipment and technique, which result in score loss that increase faster than linearly with distance.